2008
DOI: 10.1021/ja8008924
|View full text |Cite
|
Sign up to set email alerts
|

Two Color RNA Intercalating Probe for Cell Imaging Applications

Abstract: Here we report on a phenanthridine derivative which has a covalently linked fluorescein molecule in order to increase the light absorption and hence fluorescence signal intensity when bound to duplex RNA. Steady-state fluorescence shows that the energy transfer efficiency from the fluorescein to the phenanthridine fluorophore is approximately 77%, which results in the probe being over 5x brighter than other phenanthridine derivatives when bound to RNA. Due to the relatively long lifetime (approximately 20 ns) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(76 citation statements)
references
References 12 publications
3
73
0
Order By: Relevance
“…Many of the dead and dying cell images with probes 1 and 2 showed punctate regions of high fluorescence intensity in the nucleus that were reminiscent of the nucleolus staining observed with RNA targeting probes. 4041 Similar cell staining patterns with probe 1 were observed using dead and dying MDA-MB-231 breast cancer cells that had been treated with the drug etoposide (Figure S7). …”
Section: Resultssupporting
confidence: 63%
“…Many of the dead and dying cell images with probes 1 and 2 showed punctate regions of high fluorescence intensity in the nucleus that were reminiscent of the nucleolus staining observed with RNA targeting probes. 4041 Similar cell staining patterns with probe 1 were observed using dead and dying MDA-MB-231 breast cancer cells that had been treated with the drug etoposide (Figure S7). …”
Section: Resultssupporting
confidence: 63%
“…4 In addition, it was shown that the chemical modulation of the phenanthridine exocyclic amines is a profitable option to tune the nucleic acid recognition properties of phenanthridinium dyes. 5 A lot of experimental data on ethidium derivatives have been collected over the last three decades 6 including a design of two-colour RNA intercalating probe for cell imaging applications 7 , photoaffinity labelling 8 and antibiotic as well as antitumor activity. [9][10][11][12] Also, recent study demonstrated that double amine-guanidine substitution at the 3 and 8 positions of the ethidium bromide changed the original intercalator into a minor groove binder of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…25 Therefore, we decided to study an influence of biguanide substituents attached to the 3 and/or 8 position of the phenanthridine ring (compounds 5, 6; Scheme 1) on the binding mechanism of these ligands to DNA/RNA and on their cytotoxic activity. Moreover, to investigate the impact of biguanide-substituents, obtained results are compared with previously studied analogues (Scheme 1) equipped either with inert aliphatic substituents (7,8) or binding-active urea substituent (9). Furthermore, the antiproliferative activity of biguanide-phenanthridine conjugates against tumour cell lines and normal cells was also assayed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of energy transfer in combinations of pyrene-perylene, two different coumarine dyes, and fluorescein-ethidium bromide, have been carried out with applications in biological imaging and bioanalytical science (Takakusa et al, 2003;Fujiwara et al, 2005;de Almeida et al, 2007;Stevens et al, 2009). Overlap of the fluorescence and absorption was estimated from our experiments as 6.9 × 10 −15 mol −1 cm 6 (Figure 8), and the critical Förster radius was calculated as 3.1 nm.…”
Section: Förster Energy Transfermentioning
confidence: 90%